2012
DOI: 10.5539/ijbm.v7n11p56
|View full text |Cite
|
Sign up to set email alerts
|

The Global Financial Crisis and M&A

Abstract: The global financial crisis is changing the landscape for mergers and acquisitions (M&A) and identifying new M&A targets that indicate a shift with significant impact to our global business practices. Even more now than ever before, companies are implementing strategies that include gaining access to new geographies. They are responding to the crisis by focusing on growth outside their home country regions, expanding their geographic diversification and investment in secondary markets. Previous M&A activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The failure of well-known financial institutions during the global financial crisis of 2007-2009 resulted in a freeze in global credit markets. This negative shock on the external supply of finance caused a sharp reduction in firms' cash holdings (Grave, Vardiabasis, & Yavas, 2012). Using survey data from 1,050 chief financial officers (CFOs) in the US, Europe and Asia, Campello, Graham, and Harvey (2010) found that around 86 per cent of constrained firms forwent and cancelled valuable investments during the global financial crisis.…”
Section: Cash Holdings and The Financial Crisismentioning
confidence: 99%
“…The failure of well-known financial institutions during the global financial crisis of 2007-2009 resulted in a freeze in global credit markets. This negative shock on the external supply of finance caused a sharp reduction in firms' cash holdings (Grave, Vardiabasis, & Yavas, 2012). Using survey data from 1,050 chief financial officers (CFOs) in the US, Europe and Asia, Campello, Graham, and Harvey (2010) found that around 86 per cent of constrained firms forwent and cancelled valuable investments during the global financial crisis.…”
Section: Cash Holdings and The Financial Crisismentioning
confidence: 99%
“…During a recession, the market is depressed, and stock prices are significantly lower presenting opportunities for acquirers to make cheap acquisitions during a recession. For instance, during the economic downturn in 2008, Roche Holding Switzerland acquired Genentech Inc for $43.7bn, and Bank of America took over Merrill Lynch for $48.8bn in what analysts consider as opportunistic acquisitions (Grave, Vardiabasis & Yavas, 2012). This also involves taking advantage of prevailing market situations in foreign economies to make cross-border acquisitions for organizations in pursuit of diversification.…”
Section: Timing Of Mandamentioning
confidence: 99%
“…Previous investment activity in the 20th century was mainly focused in the triad of US, Europe, and Japan, the world's largest consumer markets. However, as the triad's share of the global consumer market declines and diversification opportunities diminish, companies are looking deeper into the supply chain to identify investment opportunities and acquisition targets in other parts of the world to diversify risk, and maximize control, efficiencies, and productivity (Grave et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%